OPTIMALISASI ASET DENGAN METODE HIGHEST AND BEST USE (STUDI KASUS DI JALAN PRAMBANAN-PIYUNGAN) - Khoirudin, Rifki (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
The purpose of this study is to determine the highest and best use of assets that have not been optimized belonging to the Sleman Regency Government, which is located on Jalan Prambanan-Piyungan, Jobohan, Bokoharjo, Prambanan, Sleman, Yogyakarta Special Region. This analysis requires 4 (four) analyzes, namely physical feasibility analysis, permitted by law and/or regulation, financial feasibility and producing maximum productivity. The population of this study/study comes from the Regional Finance and Assets Agency (BKAD) of Sleman Regency as a result of Land Consolidation or others. The determination of the sample is based on problems that occur on land that have not been optimized and recommendations for the BKAD asset sector in Sleman Regency. The data needed is obtained from field observations and agencies related to research concepts such as the Spatial and Regional Plan (RTRW) of Sleman Regency, Spatial Pattern Plan / Spatial Detail Plan (RDTR) of Prambanan District and others. Data analysis uses Discounted Cash Flow (DCF) calculations such as Net Present Value (NPV), Internal rate of Return (IRR), Payback Period and with development preparation using new construction costs based on MAPPI's Technical Building Costs (BTB). The test results in the cost of a new construction of IDR 1,411,940,630, NPV > 0, IRR> Discount Rate, Payback Period 8.7 with information NPV > 0 and IRR > Discount Rate the project is feasible to run and the investment payback period is 8 years 7 month.